Kinetics of the fischer esterification of palm fatty acids with isopropanol and butyl-cellosolve - Moya León, Alonso (Universidad de Costa Rica, 2009)
Fischer esterification of the mixture of palm fatty acids can be achieved in 80% conversion, under conditions of reactive distillation and methanesulphonic acid as catalyst. The volatility of the H2O/alcohol azeotrope by-product confines the kinetic acceleration, relative to batch conditions.